German Economy Winter 2022 - Recovery temporarily on hold - Jens Boysen-Hogrefe; Dominik Groll; Timo Hoffmann; Nils Jannsen; Stefan Kooths; Nils Sonnenberg; Vincent Stamer (Kiel Institute for the World Economy (IfW Kiel), 2022)
Wholesale prices for gas and electricity have fallen significantly in recent months - even though they are still at a high level. In addition, the burdens on private households and companies caused by high energy costs are to be cushioned by so-called price brakes. Overall, inflation in 2023 will be much lower at 5.4 percent than we had expected in our autumn forecast (8.7 percent). Although real disposable income and, as a result, private consumption are likely to decrease next year, the decline will be much smaller than had been expected a few months ago. As a result, we now expect a slight increase in GDP of 0.3 percent for 2023 (autumn: -0.7 percent). In 2024, GDP is expected to grow somewhat more strongly again at 1.3 percent (autumn: 1.7 percent). The labour market is robust despite the economic slowdown, partly because companies are still desperately seeking skilled workers. The public fiscal balance is likely to deteriorate significantly in 2023 due to the aid packages in response to the energy crisis and displays a deficit of around 4 percent relative to GDP. With the expiry of the aid packages, the deficit will decrease again in 2024.
Keywords: 330; energy crisis; advanced economies; emerging economies; monetary policy; Business Cycle Germany; Fiscal Policy & National Budgets; Germany; Labor Market